2009
DOI: 10.1128/mcb.00374-09
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinoblastoma Cell Adhesion Associated with Optic Nerve Invasion

Abstract: In the 1970s, several human retinoblastoma cell lines were developed from cultures of primary tumors. As the human retinoblastoma cell lines were established in culture, growth properties and changes in cell adhesion were described. Those changes correlated with the ability of the human retinoblastoma cell lines to invade the optic nerve and metastasize in orthotopic xenograft studies. However, the mechanisms that underlie these changes were not determined. We used the recently developed knockout mouse models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 25 publications
(45 reference statements)
1
35
0
Order By: Relevance
“…Both KDM5A shRNA and PGC-1α overexpression resulted in reduced cell growth in osteosarcoma, cervical carcinoma, retinoblastoma, and SCLC cell lines. Differentiation of retinoblastoma cell lines is manifested in increased cell adhesion and requires special techniques that were not applied in our analysis by light microscope (Laurie et al 2009). However, in cases with the KDM5A knockdown, we recorded increased MFN2 expression, indicating that retinoblastoma cells respond to KDM5A loss by increasing mitochondrial fusion protein similar to other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Both KDM5A shRNA and PGC-1α overexpression resulted in reduced cell growth in osteosarcoma, cervical carcinoma, retinoblastoma, and SCLC cell lines. Differentiation of retinoblastoma cell lines is manifested in increased cell adhesion and requires special techniques that were not applied in our analysis by light microscope (Laurie et al 2009). However, in cases with the KDM5A knockdown, we recorded increased MFN2 expression, indicating that retinoblastoma cells respond to KDM5A loss by increasing mitochondrial fusion protein similar to other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that the adherent cells lacked the astrocyte marker GFAP, yet this was consistent with the progressive loss of GFAP in freshly explanted Pax2 ϩ retinal astrocytes under the same tissue culture conditions (data not shown). As these cells grew quite robustly, it is plausible that adherent cells that were previously cultured from retinoblastomas 34 or from mouse retinal tumors 46 constituted a similar retinal astrocyte population.…”
Section: Retinoblastoma Glia Have Properties Of Non-neoplastic Retinamentioning
confidence: 99%
“…Laurie et al proved this association at molecular basis, and their "detailed analysis of these cells as they were propagated in culture from the primary tumor shows that changes in cadherin-mediated cell adhesion are associated with retinoblastoma invasion of the optic nerve prior to metastasis. In addition, the same changes in cadherin-mediated cell adhesion correlate with the invasive properties of the human retinoblastoma cell lines isolated decades ago, providing a molecular mechanism for these earlier observations" [18]. In another study, it was seen that relating the RB gene expression with the clinico-pathologic features of the tumor tissues, and found that the tumor with invasion of choroid, optic nerve and retinal pigment epithelium, had relatively higher gene expression, when compared with the tumor with only choroidal invasion [19].…”
Section: Discussionmentioning
confidence: 82%